2021
DOI: 10.1001/jamanetworkopen.2021.4132
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bcr-Abl Tyrosine Kinase Inhibitors With Hepatitis B Virus Reactivation Requiring Antiviral Treatment in Taiwan

Abstract: IMPORTANCE The US Food and Drug Administration (FDA) highlighted the potential risk of hepatitis B reactivation that was associated with Bcr-Abl tyrosine kinase inhibitor (TKI) treatment and has required updated product labels. OBJECTIVE To examine the association between hepatitis B flare and exposure to Bcr-Abl TKIs compared with non-Bcr-Abl TKIs. DESIGN, SETTING, AND PARTICIPANTS This nested case-control study included patients who entered a hepatitis B carrier cohort in Taiwan after January 1, 2005. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Some cases resulted in acute hepatic failure or fulminant hepatitis leading to liver transplantation or a fatal outcome. Recently, a nested casecontrol study which included patients who entered a hepatitis B carrier cohort in Taiwan confirmed this risk [84]. This analysis revealed that BCR-ABL PKIs use during the previous 90 days was independently associated with a 56% higher risk of hepatitis B flare (adjusted rate ratio [aRR], 1.56, CI95% [1.11-2.20]).…”
Section: Hepatitis B Virus Reactivation and Bcr-abl Pkismentioning
confidence: 82%
“…Some cases resulted in acute hepatic failure or fulminant hepatitis leading to liver transplantation or a fatal outcome. Recently, a nested casecontrol study which included patients who entered a hepatitis B carrier cohort in Taiwan confirmed this risk [84]. This analysis revealed that BCR-ABL PKIs use during the previous 90 days was independently associated with a 56% higher risk of hepatitis B flare (adjusted rate ratio [aRR], 1.56, CI95% [1.11-2.20]).…”
Section: Hepatitis B Virus Reactivation and Bcr-abl Pkismentioning
confidence: 82%
“…(2) The Bcr‐Abl TKI users had at least one of the following cancer types before the index date: CML, GIST, monocytic leukemia (ML), acute lymphoblastic leukemia (ALL), or acute myeloid leukemia (AML). If a patient had more than one cancer diagnosis before the index date, the cancer type was determined according to the following hierarchical order: ALL, AML, ML, CML, GIST 11 . (3) The cancer patients using Bcr‐Abl TKIs were chronic HBV carriers, as defined according to the operational definitions described in our previous publication 11 .…”
Section: Methodsmentioning
confidence: 99%
“…If a patient had more than one cancer diagnosis before the index date, the cancer type was determined according to the following hierarchical order: ALL, AML, ML, CML, GIST 11 . (3) The cancer patients using Bcr‐Abl TKIs were chronic HBV carriers, as defined according to the operational definitions described in our previous publication 11 . The date that a patient was first recognized as HBV carrier could be before or after the index date.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two large-scale retrospective studies evaluating the risk of HBV reactivation in TKI-treated CML patients with positive HBsAg reported HBV reactivation rates of 26-34.8% (61,62). More recently, a nationwide nested casecontrol study with 733,691 patients with HBV in Taiwan found that Bcr-Abl TKI use was independently associated with HBV reactivation (aHR, 1.56; 95% CI 1.11-2.20) (63).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%